The partner’s experiences of childbirth in countries with a highly developed clinical setting : a scoping review - Nadine Schmitt; Sabine Striebich; Gabriele Meyer; Almuth Berg; Gertrud M. Ayerle (BMC pregnancy and childbirth, 2022)
Background In Western countries, it is common practice for a woman to be supported by a trusted person during childbirth, usually the other parent. Numerous studies have shown that this has a positive effect both on the woman’s satisfaction with the birth process and on physical outcomes. However, there is little research on the birth experience of partners and their wellbeing. The aim of this review is to summarise the existing literature on partner experience, consider its quality and identify the underlying themes. Methods Both a systematic literature search in three databases and a manual search were conducted, for qualitative, quantitative, and mixed-methods studies from Western countries examining the experiences of partners present at a birth. Results A total of 35 studies were included. Only one study included same-sex partners (the other studies addressed fathers’ experiences only) and only one validated questionnaire examining partners’ birth experiences was identified. Four major themes were found to influence partners’ birth experiences: (1) intense feelings, (2) role of support, (3) staff support, and (4) becoming a father. Conclusions Partners may feel very vulnerable and stressed in this unfamiliar situation. They need emotional and informal support from staff, want to be actively involved, and play an important role for the birthing woman. To promote good attachment for parents, systematic exploration of the needs of partners is essential for a positive birth experience. Because of the diversity of family constellations, all partners should be included in further studies, especially same-sex partners.
Keywords: Partner; Support person; Midwifery; Childbirth experience; Fathers; Review